Phylogenetic Study of VP6 Gene of Bovine Rotavirus A and Molecular Survey of Bovine Rotaviruses B and C, and Human G and P Genotypes of Rotavirus A in Calves in Iran - Ahmad Nazaktabar (Alborz University of Medical Sciences, 2020)
Background: Rotavirus (RV) is one of the most important causes of diarrhea in the calf and human neonates. Rotaviruses are divided into nine different serogroups, of which group A is more important compared to other groups. Objective: This study was performed because of the lack of information about the importance and prevalence of bovine rotaviruses B (RVB) and C (RVC) and human genotypes of rotavirus A (RVA) in the bovine population in Iran. Phylogenetic analysis of VP6 of bovine RVA was the second aim of the present study. Materials and Methods: A total of 581 stool specimens were collected from diarrheic calves of 14 provinces and were analyzed by reverse transcription polymerase chain reaction (RT-PCR) and 485 of them were investigated by PAGE electrophoresis to determine the frequency of three rotaviruses A (RVA), B (RVB), and C (RVC). The presence of human G and P genotypes in Iranian bovine population was also evaluated using semi-nested multiplex RT-PCR. Results: RVA was detected by RT-PCR (VP6 gene detection) in 16.2% (94/581) and by PAGE in 22.16% (108/485) and no positive cases of RVB and RVC were confirmed by polyacrylamide gel electrophoresis (PAGE). This study showed that non-A RV groups (B and C) have little role in calf diarrhea in Iran. The results of the phylogenetic study of VP6 sequences of rotaviruses A identified in this study showed that they all belonged to genotype I2 and were classified into three different branches. Specimen isolated in Zanjan showed the highest difference (maximum identity of 94%) with other sequences and clustered along with the Japanese strain, R22. Human G and P genotypes were not found in the studied samples. Conclusion: The results showed that non-A rotaviruses and human genotypes of RVA are of little importance in calf rotavirus diarrhea in Iran. Also, there is the first phylogenetic study of rotavirus A VP6 protein in Iran.